2022
DOI: 10.1002/ijc.33959
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib plus endocrine therapy significantly enhances overall survival of HR+/HER2− metastatic breast cancer patients compared to endocrine therapy alone in the second‐line setting: A large institutional study

Abstract: Cyclin‐dependent‐kinase‐4/6 inhibitor (CDK4/6i) plus endocrine therapy (ET) is standard of care for patients with advanced hormone receptor (HR)‐positive, HER2‐negative breast cancer (BC). The Breast Medical Oncology database at MD Anderson Cancer Center (MDACC) was analyzed to assess effectiveness of the CDK4/6i palbociclib plus ET compared to ET alone. From a total of 5402 advanced HR+ HER2− BC patients referred to MDACC between 1997 and 2020, we identified eligible patients who received palbociclib in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…Our study reported a mPFS between 16.0 months (in IDC) and 18.8 months (in ILC) with patients treated with CDK4/6is + AI which is lower than that reported in the PALOMA-1 (20.2 months) 27 and PALOMA-2 (24.8 months) 28 trials. This discrepancy is consistent with other reported real-world data of palbociclib in combination with ET that showed similar shorter mPFS metrics when compared with more homogeneous prospective phase 3 clinical trial data 29,30 . One of the reasons for this discrepancy may be that the PALOMA-1 and -2 trials had patients from countries with much less pretreatment (i.e., more de novo cases and less prior exposure to chemotherapy and ET) compared to our population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study reported a mPFS between 16.0 months (in IDC) and 18.8 months (in ILC) with patients treated with CDK4/6is + AI which is lower than that reported in the PALOMA-1 (20.2 months) 27 and PALOMA-2 (24.8 months) 28 trials. This discrepancy is consistent with other reported real-world data of palbociclib in combination with ET that showed similar shorter mPFS metrics when compared with more homogeneous prospective phase 3 clinical trial data 29,30 . One of the reasons for this discrepancy may be that the PALOMA-1 and -2 trials had patients from countries with much less pretreatment (i.e., more de novo cases and less prior exposure to chemotherapy and ET) compared to our population.…”
Section: Discussionsupporting
confidence: 92%
“…The median PFS and OS durations reported here were consistent with those from previous studies performed using data from the same database 29 . The mPFS and mOS durations observed with 1L CDK4/6is plus FUL (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In an observational study of a relatively younger population of patients (median age, 67 years for exposure group) in a US electronic health records database, the relative rate of OS with first‐line letrozole/palbociclib combination was significantly longer compared with letrozole alone (HR, 0.66 [95% CI, 0.53–0.82]) 7 . In another observational study representing younger patients (median age, 51 years for exposure group) from a single institution, palbociclib/aromatase inhibitor combination versus aromatase inhibitor alone did not show OS benefits in the first line, but in the second‐line setting, it was associated with a significant lower rate of all‐cause mortality (HR, 0.67 [95% CI, 0.52–0.87]) 9 . In our current analysis of older Medicare patients, the adjusted HR estimates from multivariable analyses (0.598 [95% CI, 0.428–0.834] for the first‐line setting; 0.422 [95% CI, 0.243–0.733] for second‐line setting) suggest meaningful OS benefits with CDK4/6 inhibitors, supplementing the existing data obtained from the pivotal trials and observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In another study, Ha and colleagues (2022) documented evidence of OS benefits with palbociclib from a single cancer center. 9 However, evidence from these observational studies lack generalizability in an older population of patients, such as those covered in the US Medicare system, considering the differences in population characteristics. In the older Medicare population with cancer, survival outcomes associated with novel oncology treatments have been shown to differ substantially when compared with patients represented in clinical trial, 10 further highlighting the importance of assessing these outcomes from the perspective of Medicare, which provides health care coverage to more than 55 million individuals aged 65 years and older in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation